HIV and the Antiviral Role of Mushroom Nutraceuticals - FERNANDES, Prof Dr Tito; Chaquisse, Eusébio; Ferrão, Jorge (European Journal of Applied Sciences, 2020)
Mushrooms, environment and human health are interconnected. Mushrooms’ essential role in the environment and bioremediation have attracted market attention because they are also a potential source of bioactive compounds able to perform several functions in organisms with benefits for the health of the consumer. The HIV/AIDS epidemic poses an inescapable challenge to the world at large and to Africa in particular and more specifically in Mozambique. A brief outline of the historical background discusses the present knowledge of mushrooms containing antiviral factors. Antiviral factors generally do not destroy their target pathogen; rather, they inhibit the development or reproduction of the virus. Administration of mushrooms, also used as dietary supplement extracts or biomass, supplies active immunoceuticals that may block virus cell-to-cell infection, modify viral receptors, prevent the adhesion of the virus to lymphocytes and stimulate interferon which has a general antiviral effect production and may inhibit HIV infection. Current strategies in the therapy of AIDS include antiretroviral drugs and complementary nutritional support considered beneficial. Nutrition is a fundamental part of a comprehensive package of care for people living with HIV/AIDS and mushrooms supply known bioactive molecules that may help HIV positive patients.